(untitled) (Revista NUPEART, 2025)
This text deepens reflections and methodologies for teaching color, encompassing its multiplicities, contexts, and contrasts in the teaching and learning process of an artist-teacher, grounded by the question "How to teach color and its multiplicities in a critical and reflective way?" The theoretical foundations guiding the articulation and reflection of actions are based on the concepts of experience, continuity, and interaction (Dewey, 2010, 1959, 2002, 1979), and on the a/r/tographic methodology (Irwin, 2013, 2016).